1999
DOI: 10.1086/307225
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of X‐Ray Bursts from GRS 1915+105 and Their Origin

Abstract: We report X-ray observations of the Galactic X-ray transient source GRS 1915]105 with the pointed proportional counters of the Indian X-ray Astronomy Experiment (IXAE) onboard the Indian satellite IRS-P3, which show remarkable richness in temporal variability. The observations were carried out on 1997 June 12È29 and August 7È10, in the energy range of 2È18 keV and revealed the presence of very intense X-ray bursts. All the observed bursts have a slow exponential rise, a sharp linear decay, and broadly can be p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
76
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 31 publications
8
76
1
Order By: Relevance
“…According to the most accreditated hypothesis, the disk is a thin standard one extending up to a few tens of kilometers from the central source (Fender & Belloni 2004). However, the presence of a slim disk (Abramowicz et al 1988) has also been advocated to describe some of the spectra observed from this source (Ueda et al 2009;Vierdayanti et al 2010;Yadav et al 1999). The phenomenological power-law model is used to describe a Comptonization component from an optically thick corona above the disk with an electron population containing either thermal or non-thermal particles (Zdziarski et al 2001) and where energy can be also gained from the gas bulk motion (Titarchuk et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…According to the most accreditated hypothesis, the disk is a thin standard one extending up to a few tens of kilometers from the central source (Fender & Belloni 2004). However, the presence of a slim disk (Abramowicz et al 1988) has also been advocated to describe some of the spectra observed from this source (Ueda et al 2009;Vierdayanti et al 2010;Yadav et al 1999). The phenomenological power-law model is used to describe a Comptonization component from an optically thick corona above the disk with an electron population containing either thermal or non-thermal particles (Zdziarski et al 2001) and where energy can be also gained from the gas bulk motion (Titarchuk et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been exhibiting different types of X-ray variability characteristics (Morgan, Remillard, & Greiner 1997;Muno et al 1999;Yadav et al 1999;Belloni et al 2000a). The radio emission from this source also demonstrates its chaotic nature by means of time to time huge radio flares (Mirabel & Rodriguez 1994;Fender et al 1999), long episodes of Send offprint requests to: S.V.…”
Section: Introductionmentioning
confidence: 99%
“…Fender et al (1999) suggested that the repeated ejections of the inner accretion disk (Belloni et al 1997) might be responsible for such flares. It was pointed out that such oscillations, having hard dips are not always accompanied by high radio emission Yadav et al 1999). This suggests that some other mechanism is responsible for such huge radio flares.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic features of these QPOs suggest that such oscillations are a diagnostic of the accretion processes in the inner regions of the accretion disks around the central compact objects, like shock oscillations in sub-Keplerian advective accretion disks (Chakrabarti & Titarchuk 1995, hereafter CT;Molteni, Sponholz, & Chakrabarti 1996, hereafter MSC; Kazanas, Hua, & Titarchuk 1997;Titarchuk, Lapidus, & Muslimov 1998;Chakrabarti & Manickam 2000, hereafter CM). The Galactic microquasar GRS 1915ϩ 105 shows several properties indicating that QPOs may be generated as the result of the oscillation of the hot, dense inner regions of BH accretion disks (Paul et al 1998;Muno, Morgan, & Remillard 1999;Yadav et al 1999;Rutledge et al 1999;Smith, Heindl, & Swank 2002). A numerical simulation by MSC revealed that for a shocked nonspherical advective BH accretion flow, if the inflow and cooling parameters are properly tuned, the postshock cooling time becomes comparable to the advection timescale from the shock.…”
Section: Introductionmentioning
confidence: 99%